Analysis Of Implementation Of Financial Management Pattern Of Regional Public Service Agency (PPK-BLUD) (Empirical Study Of UPT Puskesmas Cisitu) - Ajeng Ria Permatasari (Universitas Sebelas April, Fakultas Ekonomi dan Bisnis, 2023)
The Regional Public Service Agency Financial Management Pattern is a financial management pattern that provides flexibility in the form of discretion to apply sound business practices to improve services to the community in order to promote general welfare and educate the nation's life. The purpose of this study was to determine the level of implementation of PPK-BLUD flexibility that has been implemented at the Cisitu Inpatient Health Center and the obstacles encountered in the implementation process. The research method used in this research is descriptive qualitative with a case study approach. Data collection techniques used are Observation, Interview and Documentation. The results of the study show that the flexibility that has been implemented is flexibility in income, spending, procurement of goods and services, management of receivables, management of human resources (HR), cooperation, and SiLPA. While the flexibility that has not been implemented is the flexibility of debt, investment, remuneration, service rates. This is due to limited human resources in managing finances, minimal local government regulations regarding technical guidelines for BLUD implementation and lack of synergy between stakeholders in optimizing the implementation of BLUD flexibility.